Investigating ideology through framing: a critical discourse analysis of a critical literacy lesson. Issue 2 (2nd April 2020) - Weninger, Csilla
ABSTRACT: This paper examines classroom discourse from English lessons that implemented a critical literacy unit focused on a contextualised social issue. Utilising the theoretical notion of frame, the analysis of classroom excerpts highlights how ideologies about English teaching and learning at times enter the discourse of the classes, not only overtly through the teacher's talk but also through the more subtle, interactional orchestration of activities. These ideologies, it is argued, pedagogically position the lessons with reference to a procedural, exam-oriented frame, undermining the potential of the content of the talk and the critical literacy unit. Two key implications are drawn from the analysis. First, that in settings with deeply entrenched pedagogic traditions of standards, exam-focused literacy and the attendant instrumentalist view of language education, critical literacy educators may find it helpful to make these ideologies themselves the target of a critical literacy curriculum. Second, it is argued that the notion of frame can be usefully drawn upon in critical analyses of classroom discourse to make visible and understand how ideology as an interpretive framework shapes classroom talk and the learning made possible by that talk.